The Significance of the Islamic Education Teacher in Enhancing the Moral Development of Junior High School Students - Yusuf, Muhammad (Anjasmoro: Islamic Interdisciplinary Journal, 2023)
Morals are a priority in Islam. This is based on the rule that the Prophet Muhammad was sent to the world as one of his main missions to perfect morals. In achieving a person's moral perfection, guidance is needed through education, namely Islamic education. There is a problem, namely some grade VIII students of A Junior High School in Mojokerto who have bad behavior towards friends, and teachers and do not obey school rules. This study aims to determine the role of Islamic education teachers in improving the morals of class VIII students at A Junior High School in Mojokerto. The type of research used by the author is qualitative field research. Data collection techniques used in this study were interviews/interviews, documentation, and observation. The results of the study can be concluded as the role of the Islamic Education (PAI) teacher in improving the morals of class VIII students at A Junior High School in Mojokerto. PAI teachers carry out their duties in a professional, responsible, patient, and sincere manner. So, class VIII students at A Junior High School in Mojokerto, who used to have poor morals, are now better, now they become individuals who have a polite attitude.